PENGARUH AI (ARTIFICIAL INTELEGENCE) TERJEMAH TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN BAHASA ARAB - Muhammad, Nawawi Aulia; Mufidah, Nuril (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the effect of using Artificial Intelligence (AI) as a medium for Arabic translation on students' critical thinking skills. Using a quantitative descriptive approach, data was collected through a questionnaire distributed to 31 7th-semester students in the 2024/2025 academic year. The results showed that the majority of students have a positive perception of the use of AI, with 48.4% agreeing and 29% strongly agreeing that AI is effective in supporting the translation process. In addition, 25.8% of respondents strongly agreed that AI helped them understand Arabic texts, while 45.2% felt that AI encouraged in-depth analysis of text structures. In the evaluation aspect, 38.7% of students felt that they were able to judge the quality of AI-generated translations. The study also found that AI contributed to the development of students' creative thinking skills, with 67.7% of respondents finding it helpful in developing new ideas in Arabic writing. Overall, these results show that AI not only improves translation efficiency but also plays an important role in developing students' critical thinking skills, although there are still challenges that need to be overcome to maximize its utilization.